2014
DOI: 10.1111/apm.12220
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of hidradenitis suppurativa (acne inversa): a histological study of 27 patients

Abstract: Hidradenitis suppurativa (acne inverse) (HS) is a chronic skin disease primarily affecting hair follicles. The aetiology of HS is unknown, but infection is believed to play some role. This retrospective study investigated the microbial colonization directly in skin appendices in HS skin samples. Archival samples from 27 patients with HS were screened by immunofluorescence labelling with monoclonal and polyclonal antibodies against Gram-positive bacteria, Propionibacterium acnes and Propionibacterium granulosum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 29 publications
4
49
0
Order By: Relevance
“…Some studies, usually circumventing the risk of contamination by aspirating pus from deep parts or by vaporization level by level with CO 2 laser showed that coagulase-negative staphylococci and anaerobic bacteria were the main bacteria recovered from HS lesions [56,57,58]. Therefore, bacterial infection is considered to be implicated in the secondary pathogenesis of HS, and since patients with HS often require long courses of antibiotics with only partial improvement in their skin, it seems likely that HS is a biofilm disease [59,60,61,62]. Biofilms are specialized communities of bacteria showing irreversible binding to external substrates through secretion of a sticky polysaccharide matrix that surrounds and protects the community from outside insults, including antibiotics [62].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies, usually circumventing the risk of contamination by aspirating pus from deep parts or by vaporization level by level with CO 2 laser showed that coagulase-negative staphylococci and anaerobic bacteria were the main bacteria recovered from HS lesions [56,57,58]. Therefore, bacterial infection is considered to be implicated in the secondary pathogenesis of HS, and since patients with HS often require long courses of antibiotics with only partial improvement in their skin, it seems likely that HS is a biofilm disease [59,60,61,62]. Biofilms are specialized communities of bacteria showing irreversible binding to external substrates through secretion of a sticky polysaccharide matrix that surrounds and protects the community from outside insults, including antibiotics [62].…”
Section: Pathogenesismentioning
confidence: 99%
“…Biofilms are specialized communities of bacteria showing irreversible binding to external substrates through secretion of a sticky polysaccharide matrix that surrounds and protects the community from outside insults, including antibiotics [62]. Biofilms adherent to sinus tract epithelium and hair follicles have been reported in HS, supporting the hypothesis that biofilms may play a secondary role in the pathogenesis of HS, thereby making bacterial eradication more difficult [60,61]. Although this concept is very fascinating and promising, more research efforts are needed to clarify its role in HS pathogenesis.…”
Section: Pathogenesismentioning
confidence: 99%
“…Although studies point to an initial sterile process, a broad spectrum of bacteria have been found in mature HS lesions [16,17,18,19,20,21,22]. Significant bacterial infections may influence the levels of immature neutrophils in peripheral blood, and chronic bacterial infection is mostly not accompanied by increased neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…56 A retrospective study of 27 patients using histopathology found biofilm-like structures in one-fifth of the samples. 59 It is also possible that chronic HS lesions may resemble an environment such as one produced by a foreign body promoting and maintaining bacterial growth. 56 No yeasts or other infectious agents were found to play an important role in the pathogenesis.…”
Section: -Microbiologymentioning
confidence: 99%
“…56 Whether bacterial colonization is a primary or a secondary event of an initially sterile process is still a subject of much debate. 56,59 8. COMORBIDITIES As a chronic inflammatory dermatosis, HS is associated with a variety of concomitant and secondary diseases.…”
Section: -Microbiologymentioning
confidence: 99%